Penerapan Pasal 127 Undang-Undang Nomor 35 Tahun 2009 Terhadap Penyalahgunaan Narkotika Pada Proses Pemeriksaan Perkara Pidana (Studi Pada Polresta Pulau Ambon dan Pulau-Pulau Lease) - Manuputty, Gloria Imanuella; Taufik, Iqbal (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2024)
Introduction: Currently, Indonesia is experiencing the development of transnational crime distribution networks, one of which is narcotics crime. The crime of narcotics abuse is a big problem that often occurs among society and is a concern for the Indonesian nation today. Narcotics abuse is regulated in Law Number 35 of 2009 concerning Narcotics, such as one case of abuse committed by Arielson Radjawane alias Marsel. Marsel was arrested by the Ambon Island and Lease Island Narcotics Research Unit for allegedly carrying, possessing, storing or controlling marijuana. Marsel was given a prison sentence of two years and six months. Purposes of the Research: The aim of this research is to determine the handling of cases against perpetrators of narcotics abuse at the Ambon Island and Lease Island Police and to find out the basis for investigators in applying article 127 to narcotics abuse.Methods of the Research: The research method used is normative juridical, the research type is analytical descriptive with the legal materials used being primary, secondary and tertiary. The technique for collecting legal materials uses literature study, analysis of legal materials uses qualitative methods. Results / Findings / Novelty of the Research: The results of this research can be concluded that the handling of cases against perpetrators of narcotics abuse at the Ambon Island and Lease Island Police can be handled and given criminal sanctions based on the legal provisions of Article 127 of Law Number 35 of 2009 concerning Narcotics. And the application of article 127 of Law Number 35 of 2009 concerning narcotics is sufficient to provide a deterrent effect on abusers by subjecting the perpetrator to imprisonment or rehabilitation